Investigation of Plasma cell‐free cancer genome chromosomal instability as a tool for targeted minimally invasive biomarkers for primary liver cancer diagnoses. (27th May 2020) - Feng, Shuang; Ding, Zhiwen; Wang, Jin; Qian, Ziliang; Li, Shanshan; Zhang, Cunzhen; Xin, Haibei; Liu, Shupeng; Ding, Guanghui; Hu, Minggen; Meng, Yan; Li, Nan
Abstract: Purpose: To characterize plasma cell‐free cancer genome chromosomal instabilities (CIN) in patients with liver cancer and to evaluate the potential of CIN as minimally invasive biomarkers for primary liver cancer (PLC) diagnoses. Experimental Design: We collected 196 plasma samples from 172 individuals in two cohorts, a discovery cohort of surgery ineligible PLC patients and a validation cohort of hepatectomy patients with pathological disease confirmations. All samples were subjected to HiSeq X10 sequencing followed by a customized bioinformatics workflow Ultrasensitive Chromosome Aneuploidy Detection (UCAD). Results: In the discovery cohort, 29 significant copy number changes were identified in plasma from surgery‐ineligible PLC. Twenty‐two (95.7%) surgery‐ineligible liver cancers were identified as harboring copy number changes in at least 1 of 29 segments. Meanwhile 40/41 (97.6%) noncancers harbored no changes. In the validation cohort, 54 (69.4%) surgery‐eligible liver cancers were identified with positive screening, all of which were subsequently confirmed as cancer by pathological examination. Moreover, 26/27 = 96.3% noncancers were identified with negative screening. UCAD‐positive screening was significantly associated with microvascular invasion (OR > 10, 95% CI:[2.53, ]), tumor stages B and C (OR = 8.59, 95% CI [1.07, 400]), and tumor size ≥ 3 cm (OR = 5.68, 95% CI [1.43, 28.1]). Furthermore, we collected 29 followed‐up plasma samples from 19 postsurgery patients. Nine (31.0%) postsurgery samples from 6 (31.5%) patients were identified with positive screening. Among them, 3 patients (50.0%) with positive screening were then confirmed as having disease recurrences. Conclusions: In addition to AFP, plasma cell‐free DNA sequencing is a useful tool for primary liver cancer diagnoses. Abstract : In addition to AFP, plasma cell‐free DNA sequencing is a useful tool for primary liver cancer diagnoses.